2015
DOI: 10.1007/s10811-015-0749-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Chlamydomonas reinhardtii biomass concentration from chord length distribution data

Abstract: A novel method to estimate the concentration of Chlamydomonas reinhardtii biomass was developed. The method employs the chord length distribution information gathered by means of a focused beam reflectance probe immersed in the culture sample and processes the data through a feedforward multilayer perceptron. The multilayer perceptron architecture was systematically optimised through the application of a simulated annealing algorithm. The method developed can predict the concentration of microalgae with accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In this context, ANNs have been treated as a powerful computational tool, since they can deal with nonlinear relationships, which are typical for most ecological relationships (Gevrey et al 2003;Gebler et al 2014). Artificial neural networks have been used in studies on organisms from freshwater ecosystems (e.g., Park et al 2003;Penczak et al 2012;Gebler et al 2014;Lopez-Exposito et al 2016); however, no further study has yet been conducted to confirm the performance of this approach in predicting the structure (richness and abundance) of lotic macroalgae communities, which are among the most important primary producers and are promising bioindicators of the trophic state in continental running water (Branco and Pereira 2002;Peres et al 2010;Cantonati et al 2012;Stancheva et al 2012). In this study, we showed that some architectures of multilayer ANNs were relatively efficient in predicting the species richness and abundance of macroalgae, even in high dynamic systems such as streams.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ANNs have been treated as a powerful computational tool, since they can deal with nonlinear relationships, which are typical for most ecological relationships (Gevrey et al 2003;Gebler et al 2014). Artificial neural networks have been used in studies on organisms from freshwater ecosystems (e.g., Park et al 2003;Penczak et al 2012;Gebler et al 2014;Lopez-Exposito et al 2016); however, no further study has yet been conducted to confirm the performance of this approach in predicting the structure (richness and abundance) of lotic macroalgae communities, which are among the most important primary producers and are promising bioindicators of the trophic state in continental running water (Branco and Pereira 2002;Peres et al 2010;Cantonati et al 2012;Stancheva et al 2012). In this study, we showed that some architectures of multilayer ANNs were relatively efficient in predicting the species richness and abundance of macroalgae, even in high dynamic systems such as streams.…”
Section: Discussionmentioning
confidence: 99%
“…Other estimated variables are the pigment and lipid content, and for their estimation, physical measurements of cell count, nitrate and glucose concentration are employed, complemented by process signals obtained by various methods as measurement of turbidity, IR spectrum and fluorescence, RGB imaging and transmission spectra, NMR spectroscopy, fluorescence, hyperspectral or RGB imaging, and dielectrophoresis. [22] (2) (a) [23,24] (2) (b) [25] Color analysis (RGB) Biomass On Off…”
Section: Measurement Methods Used For On-line Monitoring Of Biological Variablesmentioning
confidence: 99%
“…Lopez-Exposito et al [23] used a focused beam reflectance probe (FBRM) [64] which measures the chord length distribution (CLD), to represent the particle length distribution and to estimate the particle size. Data were acquired in samples drawn from a PBR and were processed by a perceptron (ANN) that correlated the measured CLD with the BC obtained by gravimetry, attaining a correlation coefficient of R 2 = 0.92.…”
Section: Methods Based On Reflectance Measurementmentioning
confidence: 99%
See 2 more Smart Citations